Abnormal brain structure mediates the association between ApoE4 and slow gait among patients with pathological cognitive impairment: Results from the Ontario Neurodegenerative Research Initiative: Neuropsychiatry and behavioral neurology: Novel risk factors and novel approaches to risk in dementia. (7th December 2020) - Sakurai, Ryota; Faria‐Pieruccini, Frederico; Dilliott, Allison Ann; Hegele, Robert; Tartaglia, Carmela; McLaughlin, Paula; Binns, Malcolm; Blue, Korbin; Cornish, Ben; Sunderland, Kelly M; Beaton, Derek; Haddad, Seyyed M.H.; et al.
Abstract: Background: Presence of at least one copy of the polymorphic apolipoprotein E ε4 allele (ApoE4) increases the risk of impairments of gait performance, particularly in elderly individuals with cognitive impairment or at risk of dementia; however, its underlying neural mechanism are unclear. This study examined the association among ApoE4, gait performance, and brain structural changes among elderly individuals with cognitive impairment. Method: Overall, 269 older adults with Alzheimer's disease, cerebrovascular disease with and without cognitive impairment, and mild cognitive impairment were included from the Ontario Neurodegenerative Disease Research Initiative, who were either ApoE4 carriers (n=98) or non‐ApoE4 (n=171) carriers. Gait speed was measured using an electronic walkway; speed <1 m/s was defined as slow gait. Participants were stratified into four groups according to the presence of at least one copy of ApoE4 and slow gait. Region of interest volumes were derived by automated segmentation using a 3.0T magnetic resonance imaging system. Result: Among ApoE4 carriers, 65 (24.2%) participants had slow gait. ApoE4 carriers with slow gait showed significantly higher burden of white matter hyperintensities compared with ApoE4 carriers without slow gait. Moreover, they had significantly lower hippocampal volume and greater total sulcal cerebrospinal fluid volume compared with non‐ApoE4 carriers with slow gait. These differences remained significant despite controlling for covariates (e.g., demographic and clinical characteristics, including participant type). Conclusion: Our results suggest that brain structural changes, attributable to Alzheimer's pathology, may mediate the association between ApoE4 and slow gait among elderly individuals with pathological cognitive impairment.